1973
DOI: 10.1007/bf01869991
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Na+-dependent transport systems for sugars and amino acids. Evidence against a role for the sodium gradient

Abstract: Summary. The concept that interaction between sodium-dependent transport systems represents competition for energy inherent in the transmembrane sodium gradient was examined with the use of isolated intestinal epithelial cells. The isolated cells exhibit transport interactions which are more significant in magnitude than those which have been described for intact tissue preparations. Accumulation of 1 mu valine is inhibited 60% by 10 mM 3-OMG. Conversely, uptake of 1 mM 3-OMG is inhibited only 20% by 10 mM val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 36 publications
(67 reference statements)
2
7
0
Order By: Relevance
“…More significantly, as much as a two-to threefold valine gradient was generated during the first minute of the experiment, when cellular sodium concentration exceeded that in the medium. These gradients are somewhat greater than those observed for sugars within the same interval, and apparently reflect the faster entry rates associated with valine entry [13,14].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…More significantly, as much as a two-to threefold valine gradient was generated during the first minute of the experiment, when cellular sodium concentration exceeded that in the medium. These gradients are somewhat greater than those observed for sugars within the same interval, and apparently reflect the faster entry rates associated with valine entry [13,14].…”
Section: Discussionmentioning
confidence: 72%
“…Entry of 1 mM valine in the presence of 25 mM leucine was used as a correction for diffusional entry. This concentration of leucine appears to be sufficient to block carrier-mediated valine entry [13,14]. The difference between the entry rates in the absence of leucine and those observed with 25 mM leucine present was taken as the rate of carrier-mediated entry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alvarado (1966) and Robinson & Alvarado (1977) have propagated the idea of allosteric interactions between the binding sites for sugars and amino acids. Newey & Smyth (1964) and Kimmich & Randles (1973) proposed that the available energy was insufficient to provide for optimal, parallel function of the two transport systems. Semenza (1971), Frizzell & Schultz (1971), Murer, Sigrist-Nelson & Hopfer (1975), and Munck (1978) found that mutual inhibition could be abolished by 334 ADAPTATION OF SUGAR AND AMINO ACID TRANSPORT 335 reducing or eliminating the Na gradient.…”
Section: Resultsmentioning
confidence: 99%